The role of triceps in double poling biomechanics, an introductory study - Holmberg, J. L.; Holmberg, H. C. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Previous studies (Holmberg H. -C et al, 2005 and Holmberg L. J. & Lund A. M., 2007) of double-poling cross-country skiing show that depending on style, load distribution between m. teres major (TM) and m. latissimus dorsi (LD) changes. With a modern "wide elbow" style, TM does more of the work. But, with a classical "narrow elbow" style, LD is the more dominant muscle. In the paper by Holmberg H. -C. et al there is a discussion about elbow joint movement and triceps activation. Their measurements show that skiers using the "wide elbow" style have a smaller minimum elbow angle at pole plant, higher angular elbow-flexion velocity, higher peak pole force and were faster than skiers using the "narrow elbow" style. It is suggested that "wide elbow" style skiers utilize the triceps better due to higher preloading of the muscle. The aim of this study is to find out if there is a difference in work-load for the triceps depending on double-poling style.